Changes in choroidal vascular structure from vitreoretinal lymphoma and the intraocular cytokine level associated with clinical resolution after intravitreal methotrexate treatment. - Rae-Young Kim; Jae Hyun Park; Mirinae Kim; Young-Geun Park; Seok-Goo Cho; Young-Hoon Park (PLoS ONE)
Purpose To evaluate changes in choroidal vascular structure and aqueous cytokine levels in eyes with vitreoretinal lymphoma (VRL) after intravitreal methotrexate (MTX) treatment. Methods In this retrospective study, VRL patients who visited our hospital between October 2018 and July 2020 were reviewed. Aqueous samples were obtained before treatment and at clinical resolution after intravitreal MTX therapy. Interleukin (IL)-6 and IL-10 levels and the IL-10-to-IL-6 ratio were evaluated. Swept-source optical coherence tomographic images were obtained along with the aqueous samples. Subfoveal choroidal thickness (SFCT), total vascular area of the choroid (TCA), stromal area (SA), luminal area (LA), and choroidal vascularity index (CVI) were assessed. Results Twelve patients were enrolled (female:male-5:7). The mean age (± standard deviation) at diagnosis was 60.9±8.5 years. In the 16 eyes diagnosed with VRL, values of SFCT, TCA, LA, and SA significantly decreased after treatment (all p-values <0.05). Additionally, the aqueous cytokine IL-10 level and IL-10-to-IL-6 ratio were significantly decreased (p = 0.001 and p = 0.003, respectively). The choroidal structure in the non-treated fellow eyes did not show any significant difference. There were no further changes in SFCT, TCA, LA, or CVI that occurred during maintenance therapy. For clinical remission, the patients received 7.7±5.5 intravitreal MTX injections. The required number of injections for clinical remission was positively correlated with best-corrected visual acuity, IL-10, and IL-6 levels in the active phase (p = 0.035, p = 0.009, and p = 0.031, respectively). Conclusion Eyes with active VRL exhibited choroidal thickening with increased vascular and stromal areas that decreased after remission following MTX treatment. Higher aqueous IL-10 and IL-6 levels and lower visual acuity in the active phase may indicate the number of injections required for remission; this should be considered in the treatment of patients with VRL.